Journal of Inclusion Phenomena and Macrocyclic Chemistry - Albrecht, Markus; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Inclusion Phenomena and Macrocyclic Chemistry is the premier interdisciplinary publication reporting on original research into all aspects of host-guest systems. Examples of specific areas of interest are: the preparation and characterization of new hosts and new host-guest systems, especially those involving macrocyclic ligands; crystallographic, spectroscopic, thermodynamic and theoretical studies; applications in chromatography and inclusion polymerization; enzyme modelling; molecular recognition and catalysis by inclusion compounds; intercalates in biological and non-biological systems, cyclodextrin complexes and their applications in the agriculture, flavoring, food and pharmaceutical industries; synthesis, characterization and applications of zeolites. The journal publishes primarily reports of original research and preliminary communications, provided the latter represent a significant advance in the understanding of inclusion science. Critical reviews dealing with recent advances in the field are a periodic feature of the journal.
Keywords: Food -- Biotechnology; Organic chemistry; Crystallography; Organic Chemistry; Food Science; Crystallography and Scattering Methods